VENDIAN STRATA IN THEIR TYPE AREA - Yakobsan K.E. (My University, 1987)
In the Eastern European region Vendian strata are divisible into two complexes: the lower one, only locally developed, is composed of alternating tillites, volcanics, sandy–clay rocks and dolomites; and the upper one, of alternating sandstone, siltstone, and mudstone strata with medusoid fauna, resting transgressively on the lower complex and older rocks. The lower complex is associated with sheet glaciation; the upper one was formed in a post-glacial isostatic basin. The name ‘Vendian’ should be applied only to the upper complex; the lower one should be called ‘Waranger’.
Keywords: Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский